Completitud de la métrica de hausdorff es espacios métricos compactos. (2016)
This paper defines the Hausdorff metric on a closed and bounded subsets compact metric space. Throughout this is investigated by some topological properties as complete ness and total boundedness, for this two definitions is presented and also shown that they are equivalent finally shown that induced Hausdorff space is complete